Economic valuation of cactus pear production in semi-arid regions of Tunisia - Louhaichi, Mounir; Hassan, Sawsan; Yigezu, Yigezu; Slim, Slim; Gouhis, Fethi (2022)
Dataset about cactus pear production and economic evaluation in Tunisia. The dataset is part of a survey series, targeting farmer planting cactus across 5 countries: Tunisia, India, Jordan, Mexico and Chile.